2022
DOI: 10.7717/peerj.13590
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of anthropometric indicators of obesity to identify high blood pressure in adolescents—systematic review

Abstract: Background Anthropometric indicators of obesity have been associated with blood pressure in adolescents. However, the accuracy of anthropometric indicators of obesity for screening for high blood pressure (HBP) in adolescents is not known. Thus, the aim of the present study was to summarize the set of evidence regarding the predictive ability of anthropometric indicators of obesity to identify HBP in adolescents. Methods Searches were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Patients with BMI ≥28 (kg/m2), WC > 85 cm, WHR ≥0.82, and WHtR ≥0.5 had a significantly higher risk of increased BP. After adjusting for general data such as age, smoking, drinking, and surgery-related variables, we found that the body fat indices correlated with the BP during recovery from general anesthesia but WHtR was superior to the others (slightly more than WHR), in accordance with the correlation of these obesity indices with BP found in studies outside the anesthesia clinical setting [ [26] , [27] , [28] ]. Obesity impacts the pharmacokinetics and pharmacodynamics of anesthetic drugs [ 29 ], and since different anthropometric measures represent different patterns of fat deposition, increased fat mass increases the volume of distribution of lipophilic drugs and increases susceptibility to drug sensitivity [ 30 ].…”
Section: Discussionsupporting
confidence: 77%
“…Patients with BMI ≥28 (kg/m2), WC > 85 cm, WHR ≥0.82, and WHtR ≥0.5 had a significantly higher risk of increased BP. After adjusting for general data such as age, smoking, drinking, and surgery-related variables, we found that the body fat indices correlated with the BP during recovery from general anesthesia but WHtR was superior to the others (slightly more than WHR), in accordance with the correlation of these obesity indices with BP found in studies outside the anesthesia clinical setting [ [26] , [27] , [28] ]. Obesity impacts the pharmacokinetics and pharmacodynamics of anesthetic drugs [ 29 ], and since different anthropometric measures represent different patterns of fat deposition, increased fat mass increases the volume of distribution of lipophilic drugs and increases susceptibility to drug sensitivity [ 30 ].…”
Section: Discussionsupporting
confidence: 77%
“…10 In a cross-sectional study involving 1687 Colombian collegiate 27 In a systematic review of 10 cross-sectional studies involving 17,764 American, Asian, African, and European teens aged 10-19 years, Lima Borges et al investigated how well anthropometric measures of obesity could detect high blood pressure. 28 They found that BMI, WC, and WHtR were not very good at detecting high blood pressure in adolescents. Differences in the accuracy of obesity measures in detecting MetS between populations may be due to a variety of factors, including age, gender, race, nutritional status, different socioeconomic and cultural factors, and lifestyle choices.…”
Section: Discussionmentioning
confidence: 98%
“…Normal skinfold thickness in male patients ranges from greater than or equal to 7 mm, less than 13 mm, and greater than or equal to 13 mm as high skinfold thickness. In female patients, normal skinfold thickness ranges from greater than or equal to 9 mm, less than 17 mm, and greater than or equal to 17 mm as high skinfold thickness 18–21 . Patients were divided into normal skinfold thickness group and high skinfold thickness group according to their skinfold thickness, and there was no significant difference in basic information between the two groups.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 256 cancer patients who underwent initial intravenous infu- [18][19][20][21] Patients were divided into normal skinfold thickness group and high skinfold thickness group according to their skinfold thickness, and there was no significant difference in basic information between the two groups. Check if displacement, distortion, dislodgement issues arise and if so, remove the port or adjust the port position according to the actual situation of catheter occlusion.…”
Section: Study Subjectsmentioning
confidence: 99%